A chimeric antigen receptor-based cellular safeguard mechanism for selective in vivo depletion of engineered T cells - Svec, Mortimer; Dötsch, Sarah; Warmuth, Linda; Trebo, Manuel; Fräßle, Simon; Riddell, Stanley R.; Jäger, Ulrich; D’Ippolito, Elvira; Busch, Dirk H. (Frontiers in Immunology, 2024)
Adoptive immunotherapy based on chimeric antigen receptor (CAR)-engineered T cells has exhibited impressive clinical efficacy in treating B-cell malignancies. However, the potency of CAR-T cells carries the potential for significant on-target/off-tumor toxicities when target antigens are shared with healthy cells, necessitating the development of complementary safety measures. In this context, there is a need to selectively eliminate therapeutically administered CAR-T cells, especially to revert longterm CAR-T cell-related side effects. To address this, we have developed an effective cellular-based safety mechanism to specifically target and eliminate the transferred CAR-T cells. As proof-ofprinciple, we have designed a secondary CAR (anti-CAR CAR) capable of recognizing a short peptide sequence (Strep-tag II) incorporated into the hinge domain of an anti-CD19 CAR. In in vitro experiments, these anti-CAR CAR-T cells have demonstrated antigen-specific cytokine release and cytotoxicity when co-cultured with anti-CD19 CAR-T cells. Moreover, in both immunocompromised and immunocompetent mice, we observed the successful depletion of anti-CD19 CAR-T cells when administered concurrently with anti-CAR CAR-T cells. We have also demonstrated the efficacy of this safeguard mechanism in a clinically relevant animal model of B-cell aplasia induced by CD19 CAR treatment, where this side effect was reversed upon anti-CAR CAR-T cells infusion. Notably, efficient B-cell recovery occurred even in the absence of any pre-conditioning regimens prior anti-CAR CAR-T cells transfer, thus enhancing its practical applicability. In summary, we developed a robust cellular safeguard system for selective in vivo elimination of engineered T cells, offering a promising solution to address CAR-T cell-related on-target/off-tumor toxicities.